How Effective Is Location-Targeted Mobile Advertising? - Keith, Megan; Luo, Xueming; Fang, Zheng (MIT Sloan Management Review, 2015)
Mobile advertising that is targeted based on a consumer's location can be effective -- particularly with customers who have a high level of interest in the type of product you're selling.
Online resource; Title from title page (viewed January 1, 2015)